Democratic Republic of the Congo Economic Update, 7th Edition : Digital Inclusion for Equitable Growth; The New Telecom Law : A Key Catalyst - World Bank (Washington, DC, 2022)
The Democratic Republic of the Congo (DRC) has suffered from decades of conflict, poor governance, and volatile economic growth reflecting commodity dependence. Poverty remains widespread in the country, including in urban areas, albeit uneven across regions. The Coronavirus (COVID-19) pandemic exacerbated the DRC’s existing economic vulnerability to external shocks while boosting the use of digital technology. This 7th edition, covering the period 2020–2021 and the first quarter of 2022, examines how the DRC economy responded and fared amidst adverse shocks, with a view to improving the country’s resilience in the future. It analyzes the impact of the COVID-19 pandemic and the global recovery, as well as the most recent impact of the war in Ukraine on the DRC’s main macroeconomic aggregates. The report focuses on the importance of digital development in bringing about poverty reduction and inclusive growth. It leverages the critical breakthrough of the new Telecommunications Law to improve connectivity and close the digital divide, while exposing the remaining challenges. This economic update targets a broad audience, including decision makers, the business environment, local and international development partners, civil society actors, the academic environment, and economic and financial analysts.